Culture and HCI: a review of recent cultural studies in HCI and social networks - Kyriakoullis, Leantros; Zaphiris, Panayiotis (My University, 2016)
Studies on culture in HCI have always drawn the attention of academics. A comprehensive literature review of recent HCI studies on culture becomes a necessity. This study followed a systematic approach to review and create taxonomy of recent literature on culture from various HCI disciplines and how that relates to Social Networks. Most of the literature review focuses on recent studies on culture published in the last 5 years. The literature review reveals that understanding cultural values of people requires deep research. It highlights the complications of culture when it comes to interface design and makes some recommendations on designing more acceptable user interfaces. Understanding cultural values is essential for the design of successful and widely accepted user interfaces. The attempt of this study is to increase cultural awareness of people involved in international or cross-cultural HCI projects.
Keywords: HCI; Culture; User interface; Social networks